Trajektoria tonalno-harmoniczna jako wyraz archetypu narracyjnego unii mistycznej w twórczości Charles’a Tournemire’a i Aleksandra Skriabina - Raba, Bogusław (Res Facta Nova, 2021)
The subject of the article is a comparison of the process of transformations of the tonal-harmonic structure in the works of Alexander Scriabin and Charles Tournemire in relation to the narrative archetype of the mystical union. The justification for comparing these aspects of the work of these two composers is their development of a similar harmonic idiom, which they used to symbolically justify diametrically opposed worldviews. Scriabin’s work is considered a breakthrough for European music culture, whereas Tournemire’s is still little known. Just as the former assumed the role of composer-philosopher, the latter became a musical theologian. Tournemire, organist of the St. Clotilde basilica in Paris, initiated the tradition of musical homiletics, in which the central persuasive element, similar to the Gospel parable, was the musical narrative trajectory. Its climax was the mystical chord. However, a comparative analysis of harmonic structures, topics, narrative trajectories, shows the limits of semantization that differentiates aesthetic postulates and analogous narrative constructions, the nodal moment of which are created by the union of polarization elements.